2023
DOI: 10.1039/d2ra06931h
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive substances inhibiting COX-2 and cancer cells isolated from the fibrous roots of Alangium chinense (Lour.) Harms

Abstract: Alangium chinense has been used as a traditional folk medicine for centuries to treat rheumatism, skin diseases, and diabetes by the people of Southeast Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Similarly, Sharma and Janmeda (2017) isolated the 2‐(3,4‐dihydroxy‐5‐methoxy‐phenyl)‐3,5‐dihydroxy‐6,7‐dimethoxychromen‐4‐one from the hydro‐ethanolic extract of EN that reported to have anticarcinogenic activity. Furthermore, Alangium chinense compounds (1, 5, 12, and 21) demonstrated cytotoxicity against HepG2 cells, compounds 2 and 21 demonstrated cytotoxicity against Caco‐2 cells, and compound 20 demonstrated cytotoxicity against HeLa cells (Xiao et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Sharma and Janmeda (2017) isolated the 2‐(3,4‐dihydroxy‐5‐methoxy‐phenyl)‐3,5‐dihydroxy‐6,7‐dimethoxychromen‐4‐one from the hydro‐ethanolic extract of EN that reported to have anticarcinogenic activity. Furthermore, Alangium chinense compounds (1, 5, 12, and 21) demonstrated cytotoxicity against HepG2 cells, compounds 2 and 21 demonstrated cytotoxicity against Caco‐2 cells, and compound 20 demonstrated cytotoxicity against HeLa cells (Xiao et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a study by Li XJ et al, in 2021 suggested that Frankincense oil, derived from the Boswellia carterii plant, contains a compound with the potential to inhibit COX-2 expression in an animal model of hind paw inflammation [ 49 ]. Similarly, research involving the fibrous root of the Chinese plant Alangium chinense revealed sesquiterpenes with anti-inflammatory properties, outperforming standard drugs in terms of their effectiveness [ 50 ]. These findings suggest that natural compounds may hold the key to managing inflammation and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Harms. Recent studies have shown that monomeric compounds from Alangium chinese exhibit good inhibitory effects on HeLa cells [ 6 ]. The current research has placed significant emphasis on Alangium chinense , but insufficient with regards to AP.…”
Section: Introductionmentioning
confidence: 99%